Effects of Procurement Planning on Organizational Growth and Development - Francis Mwau (Prosiding International conference on Information Technology and Business (ICITB), 2017)
Procurement planning is integral aspect in any organization operations. It has seen many organizations succeed and others get extinct from the way it is planned, carried and implemented. It is an area that is prone to business cartels and corruption, hence no single day passes without a headline on the global dailies about a corrupt procurement deal. Procurement planning is the primary function that stage for subsequent procurement activities. The objective of this study is to examine the effects of procurement planning on organizational performance at the Kenya Methodist University (administration, human resource, ICT, internal audit, procurement and Finance) The independent variables in this study are, staff competence, top management support and management information systems. The dependent variable is growth and development of the organization. The literature review explains theories that relate to procurement planning and its effect on organizational growth and development. These theories include, the agency theory and the stewardship theory. The paper ends with an analytical summary of the two theories and how they relate with the modern procurement of resources in organizations.Keywords : Procurement, Agency Theory, Stewardship Theory.